2014
DOI: 10.1177/1758573214550838
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and accuracy of digital templating for the humeral component of total shoulder arthroplasty

Abstract: Background: This experimental study evaluated the interobserver reliability and accuracy of pre-operative digital templating for humeral head size, stem size and neck angle for total shoulder arthroplasty. Methods: Twenty-five patients underwent a total shoulder arthroplasty with a single prosthesis. Four independent, blinded surgeons (two experienced shoulder surgeons and two PGY-6 fellows) used pre-operative radiographs and templating software to generate templates of the humeral head, stem and neck for each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 25 publications
0
26
0
Order By: Relevance
“…Lee et al used digital templating on 25 patients undergoing TSA. 11 They accurately predicted stem size 36% of the time and were within one size variation in only 77% of the cases. They found interobserver reliability was only fair to moderate (kappa: 0.39-0.72).…”
Section: Discussionmentioning
confidence: 97%
“…Lee et al used digital templating on 25 patients undergoing TSA. 11 They accurately predicted stem size 36% of the time and were within one size variation in only 77% of the cases. They found interobserver reliability was only fair to moderate (kappa: 0.39-0.72).…”
Section: Discussionmentioning
confidence: 97%
“…The authors reported templating sizes for head, stem size, and neck angle matched implants within one size only 53-77% of the time. 25 A fundamental difference between the Raiss et al and the Lee et al is that the former was not assessing accuracy of implant sizes, but just reporting concordance between the plan and implant. Iannotti et al showed 3-D preoperative templating software significantly improved glenoid positioning as compared to 2-D imaging with accuracy within 5˚ of inclination and 10˚ of version.…”
Section: Discussionmentioning
confidence: 99%
“…The literature is relatively limited on use of such planning tools for prediction of implant sizes needed for a given case. 15 , 18 , 21 24 , 25 Lee, et al utilized a 2-D templating too, however, they had overall low level of agreement with pre-operative templated sizes and actual surgical implant sizes. 25 The aim of this study was to evaluate the accuracy of component size selection for both the humerus and glenoid based on digital templating using one such program (BLUEPRINT™, Wright Medical, Memphis, TN).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This results in similar accuracy when compared with analog templating, with 53% accuracy of templated head size and 77% accuracy of stem size to one size variation. 22 A 2D CT scan can be used to determine glenoid version, as previously described. These measurements can then be combined with traditional methods to estimate the required version correction angle intraoperatively.…”
Section: Glenoid Vault Modelmentioning
confidence: 99%